Daily Stock Price Behavior of Commercial Banks in Nepal - Baral, Keshar J.; Shrestha, Surya Kumar (Journal of Nepalese Business Studies, 2007)
Using the data set on daily stock prices during the fiscal year 2005/06 (July 16, 2005 through July 16, 2006), this paper attempts to analyze the stock price behavior of commercial banks in Nepalese markets. The results of serial correlation and run tests conclude that the proposition of Random Walk Hypothesis (RWH) in Nepalese stock markets does not hold true. This conclusion corroborates with the conclusions of the past studies carried out in Nepalese context. Journal of Nepalese Business Studies 2006/III/1 pp. 100-110